Rasanubhuti and Hardy’s philosophy of life - Tiwari, *Dr. Sushama (International Multidisciplinary Research Journal, 2011)
Hardy’s philosophy of life is scattered in the events, characters, situations and the atmospheric colors of his fourteen novels. It is difficult to consolidate them from the point of view of the rasa-theory; still the essence of his philosophy can be squeezed from them.